Shear bond strength of orthodontic brackets using different types of bonding materials (Mustansiria Dental Journal, 2018)
Aim: the shear bond strength testing has been accomplished to lead orthodontists in selection of adhesives and brackets. The current research was conducted to assess the effect of using different types of bonding material on the shear bond strength of plastic brackets.Materials and methods: Thirty upper first premolar teeth were utilized. There were 3 groups: - chemical composite, no mix chemical composite and light cure composite.  Samples were then subjected to shear bond test using Instron testing machine. Samples data were then analyzed and compared using ANOVA and LSD tests.Results: The results indicated that the chemical composite presented the greatest value of mean shear bond strength. On the other hand, the light cure gave the least mean shear bond strength. Highly significant differences between two groups (P≤0.01) ;and among all groups(P≤0.01)were obtained.Conclusion: Chemical composites provided a greater shear bond strength than other types of composite (no mix and light cure).